Fabricação e avaliação de um compósito cerâmico Al2O3-ZrO2-TiC em gradação funcional com WC-Co - Carli, Davi de (2023)
Functionally Graded Material (FGM) is made of two or more materials with distinct properties in a gradient form, allowing the change of properties in a given direction along the sample volume. The FGM manufacturing process is an important research theme, in which powder metallurgy (PM) highlights owing to a wide range of materials, microstructure, and shape control. This work aims to design a ceramic FGM, manufactured by PM using pulsed electric current (PECS) as a sintering technique. In addition to characterizing the stepped gradient microstructure, density, thermal conductivity, hardness, and fracture toughness. α-Al2O3 ultrafine powder, 3Y-ZrO2 and TiC nano powder, and WC-Co fine powder were the materials used to manufacture the FGM. A one-dimensional thermomechanical model was used to predict residual stress in the FGM. The samples were sintered at 1425ºC with a dwell time of 7 minutes, uniaxial pressure of 50 MPa, and vacuum atmosphere. The microstructure was mainly characterized by scanning electron microscopy after metallographic preparation. The density evaluation was performed on a precision scale using Archimedes’ principle, and the theoretical density was obtained from the inverse rule of mixtures. Vickers hardness test and fracture toughness by indentation method were carried out. Residual stress prediction indicated tensile stress in rich ceramic layers, however, below the material fracture strength. In the microscopic analysis, cracks due to residual were not observed along the microstructure. The different volume fractions of the constituents showed the stepped gradient. The average value of experimental and relative density was 6.12 g/cm³ and 98.68%, respectively. The average value of thermal conductivity was 41.42 W/mºC. A change in Vickers hardness number (26.8%) as well as in fracture toughness (35.6%) was observed along the gradient.